2011
DOI: 10.1177/1753193411426809
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the skyline view for detecting dorsal cortical penetration during volar distal radius fixation

Abstract: Fractures of the distal radius are commonly treated using volar locking plates. Several complications have been associated with this procedure, including extensor tendon irritation and rupture. It has been suggested that prominence of screws past the dorsal cortex may contribute to this complication. This study aimed to determine the ability of the skyline view to demonstrate screws penetrating the dorsal cortex. A volar locking plate was applied to a synthetic forearm model. Lateral, oblique, and skyline view… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
47
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 11 publications
3
47
1
Order By: Relevance
“…In the study by Ganesh et al, the DTV sensitivity was 100 % in detecting prominent screws in the 3rd dorsal compartment, whereas it was only 50 % in the 4th dorsal compartment and 60 % in the 2nd (23). In the study using a sawbones model, the skyline view was 83 % sensitive for detecting dorsal cortical penetration by 1 mm (24). In our study, the lowest sensitivity was found for the 4th hole and caused tenosynovitis in one case, which required a surgical revision.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In the study by Ganesh et al, the DTV sensitivity was 100 % in detecting prominent screws in the 3rd dorsal compartment, whereas it was only 50 % in the 4th dorsal compartment and 60 % in the 2nd (23). In the study using a sawbones model, the skyline view was 83 % sensitive for detecting dorsal cortical penetration by 1 mm (24). In our study, the lowest sensitivity was found for the 4th hole and caused tenosynovitis in one case, which required a surgical revision.…”
Section: Discussionmentioning
confidence: 94%
“…There are two described techniques to achieve DTV. The fi rst (and mostly used) is with the supinated forearm inclined at 15° to the vertical X-ray beam with maximum wrist fl exion (8,12,13,21,(23)(24)(25)(26). The second is with a pronated forearm and horizontally placed fl uoroscope with the X-ray beam parallel to the dorsal aspect of the distal radius (9,27).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the limitations stated above, the data presented suggest that defining standard screw lengths based on the distal radius width is feasible. While the use of screws with standardized, predetermined lengths should mostly eliminate dorsal screw protrusions, a final control using the radiographic skyline view [ 30 , 31 ] or a similar technique would remain a prerequisite.…”
Section: Discussionmentioning
confidence: 99%
“…In a study using a sawbones model, the sensitivity of the skyline view was 83% in detecting a screw crossing the dorsal cortical bone by up to 1 mm, while the sensitivity using an oblique pronation projection view was 77% and using a profile view 51%. 6 Two clinical studies using the skyline view showed a change in screw length in 4 of 15 patients 9 and 11 of 27 patients. 10 In our study the screw length was changed in 11 of 75 patients.…”
Section: Discussionmentioning
confidence: 99%
“…5 The accuracy of this view has been validated by experimental studies. [6][7][8] There are two published clinical series on the use of this view. 9,10 The purpose of this article is to demonstrate the utility of the skyline fluoroscopic view in detecting screws that penetrate the dorsal cortex of the distal radius that are not apparent on AP and lateral fluoroscopic views.…”
mentioning
confidence: 99%